POLA SERAPAN HARA DAN PERTUMBUHAN BEBERAPA VARIETAS KEDELAI DENGAN BUDIDAYA JENUH AIR DI LAHAN RAWA PASANG SURUT - Sagala, Danner; Ghulamahdi, Munif; Melati, Maya (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2011)
Saturated soil culture (SSC) technology appropriate to prevent pyrite oxidation on tidal swamps and has been proved to increase the productivity of soybean on non-tidal swamp. The objective of the research was to determine the growth response of soybean varieties under saturated soil culture on tidal swamps. The research was conducted at Banyu Urip, Tanjung Lago, Banyuasin District, and South Sumatera Province, Indonesia from April to August 2009. The experiment was arranged in a split plot design with three replications. The main-plot of the experiment was water depth in the furrow consisted of 10, 20, 30, and 40 cm under soil surface (USS). The subplot of the experiments was soybean varieties consisted of Tanggamus, Slamet, Wilis, and Anjasmoro. No-watering was arranged out of the design as a comparison. The result showed that nutrient absorption of N, K and Mn by Tanggamus was higher than those of other varieties, except K, however K absorption of Tanggamus was not significantly different from Anjasmoro. P and Fe absorption of Tangamus tended to be higher than the other varieties, although statistically they were not affected by variety. However, technically and economically, 20 cm USS was the most appropriate water depth for soybean production at tidal swamps.